2018
DOI: 10.1097/iae.0000000000001627
|View full text |Cite
|
Sign up to set email alerts
|

Residual Intraretinal Edema After 25-Gauge Vitrectomy and Macular Pucker Removal

Abstract: Intraoperative sustained-release dexamethasone implant, a powerful antiinflammatory agent with significant efficacy in vitrectomized eyes, did not result in a significant change in macular thickness and volume compared with the vitrectomy alone without dexamethasone implant at 6-month follow-up. These data support the hypothesis that its etiology does not seem to be mainly related to an inflammatory process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 27 publications
1
26
1
1
Order By: Relevance
“…A randomized, controlled trial by Guidi et al . [ 9 ] tested the effectiveness of intraoperative slow-release dexamethasone implants in improving BCVA after 25-G vitrectomy and ERM removal in patients affected by idiopathic macular pucker. After 6 months, the study indicated that although there were significant improvements in BCVA scores, and reductions in foveal thickness post-surgery, there were no significant differences between the control group and the group receiving the dexamethasone implants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A randomized, controlled trial by Guidi et al . [ 9 ] tested the effectiveness of intraoperative slow-release dexamethasone implants in improving BCVA after 25-G vitrectomy and ERM removal in patients affected by idiopathic macular pucker. After 6 months, the study indicated that although there were significant improvements in BCVA scores, and reductions in foveal thickness post-surgery, there were no significant differences between the control group and the group receiving the dexamethasone implants.…”
Section: Discussionmentioning
confidence: 99%
“…After 6 months, the study indicated that although there were significant improvements in BCVA scores, and reductions in foveal thickness post-surgery, there were no significant differences between the control group and the group receiving the dexamethasone implants. [ 9 ] However, Guidi et al . [ 9 ] did not investigate early-stage improvements in BCVA scores or reduction in foveal thickness in their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the first trigger in the development of macular edema in ERM patients seems to be more mechanical due to tractional forces of ERM on the retina. However, this mechanical distortion of the retinal surface may lead to secondary biochemical pathways, including the release of various cytokines or growth factors [23, 24]. In addition, inflammation has been proven to be induced by PPV per se in patients who undergo PPV for various etiologies [25].…”
Section: Discussionmentioning
confidence: 99%
“…The existing studies have demonstrated that the administration of intravitreal triamcinolone in patients treated with PPV for ERM removal leads to a significant decrease in CRT but does not significantly influence the visual outcomes in the majority of studies [13-15]. Noticeably, triamcinolone has been found to last approximately 113 days in vitrectomized eyes [15], while intravitreal dexamethasone implant has been shown to be 6 times more effective than triamcinolone [24]. However, Yonekawa et al [26] reported a similar trend between triamcinolone and intravitreal dexamethasone implant regarding anatomical and functional outcomes in patients affected by macular pucker and treated with PPV, although this was a retrospective study without a control group.…”
Section: Discussionmentioning
confidence: 99%